The effects of accelerator on PFA concrete/ Mohd. Zuki Isa - Isa, Mohd. Zuki (1993)
The aim of this project is to analyse the effects of accelerators on PFA concrete. Various level of PFA content are used and each, mix is cast with, a specified amount of accelerators. OPC and PFA concrete with or without accelerators is also cast as control samples. The concrete strength development is obtained from. iOO mm samples which are crushed at 3 , 7 » 23 , QO days. The 15O mm cubes are used to monitor the durability in term of its absorption properties. 1SAT test will 6e employed in determining the variations of obsorption characteristics of OPC & PFA concrete.